1990
DOI: 10.1007/bf01014094
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone variation among eastern European and a western Asian population of the turnip mothAgrotis segetum

Abstract: The female sex pheromone composition and the male electro-physiological response with respect to the three main sex pheromone components, (Z)-5-decenyl acetate, (Z)-7-dodecenyl acetate, and (Z)-9-tetradecenyl acetate, were investigated in populations ofAgrotis segetum from Armenia and Bulgaria. The percentage composition of the female-produced pheromone was 1∶52∶47 and 1∶42∶57 for the respective populations. Corresponding male receptor frequencies were 9∶90∶1 and 6∶92∶2. EAG response profiles of the male anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 18 publications
0
43
0
1
Order By: Relevance
“…From earlier investigations we know that it is indeed sufficient, with a very low percentage of neurons detecting behaviorally crucial odors (Kalinová et al, 2001;Baker et al, 2004). In the turnip moth, Agrotis segetum, approximately 1-2% of the male olfactory receptor neurons are tuned to an important pheromone component, and in this case no other neurons respond to this specific component (Löfstedt et al, 1982;Hansson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…From earlier investigations we know that it is indeed sufficient, with a very low percentage of neurons detecting behaviorally crucial odors (Kalinová et al, 2001;Baker et al, 2004). In the turnip moth, Agrotis segetum, approximately 1-2% of the male olfactory receptor neurons are tuned to an important pheromone component, and in this case no other neurons respond to this specific component (Löfstedt et al, 1982;Hansson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In this species a large variation both in female pheromone production and male sensory setup was initially shown between different parts of Europe and western Asia (60,95). However, the largest differences were found when two races, occurring north and south of the Sahara, were compared (140).…”
Section: Blend-detection In Polymorphic Systemsmentioning
confidence: 99%
“…It appears this is the case with E. lignosellus in relation to the population studied in the USA 4 . In another study, sex pheromone "dialects" have been reported in Agrotis segetum from different geographic regions 14 .…”
Section: Resultsmentioning
confidence: 99%